The experience of sexuality of male cancer patients under palliative care at Hospice Wits Houghton - Walter, Suzanne (Department of Public Health and Family Medicine, 2014)
The experience of advanced cancer leaves in its wake devastating effects, which are both complex and multi-dimensional for the patient, their family and society. The consequences are far-reaching and span psychological, physical and sexual dimensions. Unfortunately sexual dimensions are least addressed by researchers and healthcare professionals, even though most patients wish to have this area dealt with. Sexuality is a complex phenomenon that is influenced and shaped by physical, social, cultural and religious factors. The research that has been conducted on sexuality on the male cancer patient under palliative care has largely focussed on the physical aspects of sexuality such as erection, ejaculation and fertility. Studies conducted on the patients' actual experience of sexuality are few and no studies of this nature have been found to exist within the South African context.